Comorbidity profiles in association with vitiligo: a nationwide population‐based study in Taiwan. (16th December 2014) - Chen, Y.T.; Chen, Y.J.; Hwang, C.Y.; Lin, M.W.; Chen, T.J.; Chen, C.C.; Chu, S.Y.; Lee, D.D.; Chang, Y.T.; Liu, H.N.
Abstract Background The previous literature has demonstrated the association of autoimmune and atopic diseases with vitiligo, but there has been no large‐scale nationwide study conducted to confirm this. Objectives The present study was conducted to clarify the comorbid profiles in vitiligo patients and thereby better understand their clinical scenarios and underlying pathogenesis. Methods This was a retrospective population‐based study conducted from 1996 to 2011 via the National Health Insurance Research Database in Taiwan. The differences in the prevalence of multiple autoimmune and atopic diseases between case subjects and controls were analysed by multiple logistic regression method. Results A total of 14883 vitiligo patients and 59532 controls were enroled. The prevalence of vitiligo was 0.064% and the peak of onset age was 40–59 years old. The non‐stratified analysis evidenced a significant association between vitiligo and several comorbid diseases, including alopecia areata, Hashimoto thyroiditis, myasthenia gravis, psoriasis, Graves' disease, Sjögren's syndrome, systemic lupus erythematosus and atopic dermatitis. Vitiligo patients also had higher prevalence of multiple comorbidities than controls. In the age‐ and gender‐stratified analysis, increased risks of systemic lupus erythematosus and Sjögren's syndrome were observed only in subjects aged 60–79. The association of vitiligo with myasthenia gravis and rheumatoid arthritis was identified only in the subgroup aged 20–39 and in females aged 60–79 respectively. Conclusion Our study not only confirmed the significant association of vitiligo with multiple autoimmune and atopic diseases in Taiwan but also disclosed several unique findings, including the much lower prevalence of vitiligo, delayed onset of vitiligo by three decades, different associated comorbidity profiles comparing to westerners and the age‐ and gender‐specific approach for the vitiligo‐associated comorbidities.